Good Corporate Governance, Corporate Social Responsibility Disclosure, and Firm Value - Trisnawati, Rina; Sasongko, Noer; Wiyadi, W; Indrawati, Lykna (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2019)
Purpose: this study was conducted to analyze the effect of good corporate governance on disclosure of corporate social responsibility and its impact on corporate valueMethodology: This research is a study that used a quantitative approach. The population of this research was all property, real estate and building construction companies listed on Indonesian Stock Exchange during the period of 2013-2017 as many as 320 companies and the total sample is 295 companies. The sampling method used purposive sampling, The analysis data used stepwise regression.Results: Institutional ownership affects the disclosure of corporate social responsibility , while the managerial ownership, the number of the board of commissioners, the number of the audit committee do not affect the disclosure of corporate social responsibility. Disclosure of corporate social responsibility affects the value of the company,Applications/Originality/Value: GCG implementation provides support for stakeholders, community and the environment. One form of implementing corporate governance principles is the implementation of Corporate Social Responsibility (CSR). Shareholders seek to maximize the value of the company by surrendering its management to disclose its activities .CSR is one of primarily activity by management to maximize the firm value.